Effects of dietary vitamin C supplementation on fatty acid profile in breast meat of broiler chickens - Tavakoli, Masoomeh (Array, 2020)
This experiment was performed to evaluate the effects of using three different levels of vitamin C (0, 200 and 400 mg/kg) in diet on fatty acid profiles of breast meat of broilers. The experiment was performed in a completely randomized design in 3 treatments and 4 replicates with 10 chickens per pen for 42 days using 120 one-day-old male chickens of commercial Ross 308 strain. Data analysis was performed by SAS statistical software and the comparison of the means with Duncan's multiple-range test at 5% probability level. The results showed that the percentage of saturated fatty acids such as myristic acid, palmitic acid and stearic acid decreased by 200 mg/kg vitamin C. Also, the amount of unsaturated fatty acids increased at the same level of vitamin C and the saturated fatty acids were reduced.